The elderly's experiences: family support and participation in the integration of health services - Aris Wawomeo; Theresia Avila Kurnia; Sisilia Leny Cahyani; Anatolia Karmelita Doondori; Yustina Pacifica Maria Paschalia (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2023)
Background: Higher life expectancy in Indonesia alarms the government to become more serious in enhancing the implementation of community programs for elderlies. The programs are intended to improve the life quality of the elderlies. Integration of health services for the elderly program that is well-implemented will make it easier for elderlies to Purpose: To determine the relationship between family support and the active participation of elderlies in attending integration of health servicesMethod: This correlational study was performed using a cross-sectional approach on 30 elderlies as respondents who were purposively sampled. Data of this study were collected using questionnaires which were then analyzed in a univariate analysis using frequency data. Bivariate analysis was also carried out using the chi-square test. Results: Most of the respondents actively participated in the program (76.67 percent). They are aware that they are vulnerable to health problems because respondents have good family support (53.33 percent). In particular, they rated good emotional support (66.67 percent), good facility support (73.33 percent), good knowledge and information support (46.67 percent), and good appraisal support (46.67 percent).Conclusion: The data analysis indicated the presence of a correlation between family support and the active participation of elderlies in the integration of health services for the elderly program in Ende Regency.Suggestion: Public Health Center needs to raise awareness of the reluctance of elderlies in attending the integration of health services for the elderly. It is necessary that health workers visit and approach the family of elderlies in order to improve the elderly's health and quality of life.